Penyidikan terhadap Pelaku Cyberporn melalui Aplikasi Instagram - Maulana Akbar, Zen; Pratama Hapsari, Ifahda (UNES Law Review, 2023)
Technology is getting more sophisticated and more and more people are able to access and use the technology, moreover, it is not uncommon for people to abuse the technology. As is the case with the use of social media in cyberspace which is often indecent, for example the distribution of pornographic photos/pictures or even videos. Twitter, Facebook, Instagram and so on are often misused, even though the Government has stipulated rules regarding strict sanctions for perpetrators of distribution and other matters related to pornographic elements. For this reason, the author in this case examines the process of investigating cyberporn perpetrators through the Instagram application and how effective the investigation process is and the result is that the investigation process is carried out in accordance with Article 6 of the Criminal Procedure Code and is carried out on the basis of prior reports, while the level of effectiveness is influenced by three factors namely structure, substance, and legal culture. This research was conducted using normative methods obtained from secondary data sources and laws and regulations.